2022
DOI: 10.1038/s41598-022-15691-9
|View full text |Cite
|
Sign up to set email alerts
|

Age group prediction with panoramic radiomorphometric parameters using machine learning algorithms

Abstract: The aim of this study is to investigate the relationship of 18 radiomorphometric parameters of panoramic radiographs based on age, and to estimate the age group of people with permanent dentition in a non-invasive, comprehensive, and accurate manner using five machine learning algorithms. For the study population (209 men and 262 women; mean age, 32.12 ± 18.71 years), 471 digital panoramic radiographs of Korean individuals were applied. The participants were divided into three groups (with a 20-year age gap) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…AI models developed for application in pedodontics have mainly focused on: dental plaque on primary teeth ( n = 1) [ 21 ], ECC ( n = 6) [ 25 , 26 , 27 , 28 , 29 , 30 ], fissure sealant categorization ( n = 1) [ 31 ], mesiodens and supernumerary tooth identification ( n = 6) [ 3 , 10 , 22 , 23 , 24 , 41 ], chronological age assessment ( n = 4) [ 32 , 33 , 37 , 38 ], identification of deciduous and young permanent teeth ( n = 3) [ 34 , 35 , 39 ], children’s oral Health ( n = 2) [ 7 , 20 ], and ectopic eruption ( n = 2) [ 39 , 40 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AI models developed for application in pedodontics have mainly focused on: dental plaque on primary teeth ( n = 1) [ 21 ], ECC ( n = 6) [ 25 , 26 , 27 , 28 , 29 , 30 ], fissure sealant categorization ( n = 1) [ 31 ], mesiodens and supernumerary tooth identification ( n = 6) [ 3 , 10 , 22 , 23 , 24 , 41 ], chronological age assessment ( n = 4) [ 32 , 33 , 37 , 38 ], identification of deciduous and young permanent teeth ( n = 3) [ 34 , 35 , 39 ], children’s oral Health ( n = 2) [ 7 , 20 ], and ectopic eruption ( n = 2) [ 39 , 40 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lee, Y.H. et al [ 38 ] conducted an interesting study that used 18 radiomorphometric parameters extracted from panoramic radiographs (PRs) and focused primarily on developing ML algorithms. They observed that ML algorithms are more efficient at estimating age compared to traditional estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…95% CI 0.640-0.671), and random forest (0.60; 95% CI 0.583-0.611) indicated acceptable model performance. 11 Detailed information regarding the parameters used for training the models is provided in Table S1.…”
Section: Risk Factor Validation Using Machine Learning Feature Selectionmentioning
confidence: 99%
“…Galibourg [ 14 ] and Tao [ 15 ] applied machine learning to the existing scoring method for age estimation; however, this method still had a large error owing to the subjective judgment of the observer. Accordingly, attempts have recently been made to estimate age without human intervention using convolutional neural networks (CNNs) [ 18 , 19 , 20 ]. CNNs have been used to diagnose diseases such as breast cancer [ 21 ], skin cancer [ 22 ], diabetic retinopathy [ 23 ], dental caries [ 24 ], and periodontal disease [ 25 ], as well as age estimations.…”
Section: Introductionmentioning
confidence: 99%